Characterization of paleodrainages in desert regions of Saudi Arabia multisatellite images with field based study - Mashael M. Al Saud (Scientific Reports)
Abstract In Saudi Arabia, a number of linear geomorphological features with uncertain origin have been observed from space, but they do not belong to any existed drainage systems. They are ancient watercourses carried water in the past during the Holocene deluge, and they were affected by global climate change and geological processes turning them into dry and buried channels filled by sediments, and these are described as “Paleodrainages”. This study investigated these features primarily based on the integration of multi-satellite images including SRTM DEM for generating stream networks, ALOS-PALSAR which is capable to penetrate the surficial materials, and ASTER for detecting thermal differentiation in terrain surface. The novelty of this study includes the use of more than one satellite images (optical and microwave) with various spectral and optical characteristics, and this has been supported by field verification to investigate the lithological facies of stuffed materials into the detected paleodrainages, plus the classification performed for the detected paleodrainages and this has never been implemented in previous studies. Hydro-geomorphological-based categorization of these paleodrainages was carried out, indicating the majority of SW-NE trending and the presence of routes, unconsolidated sediments and rocks. From the hydrological point of view, these paleodrainages are potential for groundwater storage; and they can be also suitable sites for artificial groundwater recharge; be-sides they represent routs for saltwater intrusion on-land; and these science-based clues represent supportive element for better water resources management in Saudi Arabia.